Size and Shape of the Corpus Callosum in Adult Niemann-Pick Type C Reflects State and Trait Illness Variables - Walterfang, M.; Fahey, M.; Abel, L.; Fietz, M.; Wood, A.; Bowman, E.; Reutens, D.; Velakoulis, D. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Variable alterations to the structure of the corpus callosum have been described in adults with NPC, a neurometabolic disorder known to result in both white and gray matter pathology. This study sought to examine the structure of the callosum in a group of adult patients with NPC and compared callosal structure with a group of matched controls, and to relate callosal structure with state and trait illness variables. MATERIALS AND METHODS: Nine adult patients with NPC were matched to control subjects (n = 26) on age and sex. The corpus callosum was segmented from the midsagittal section of T1-weighted images on all subjects, and total area, length, bending angle, and mean thickness were calculated. In addition, 39 regional thickness measures were derived by using a previously published method. All measures were compared between groups, and analyzed alongside symptom measures, biochemical parameters, and ocular-motor measures. RESULTS: The callosal area and mean thickness were significantly reduced in the patient group, and regional thickness differences were greatest in the genu, posterior body, isthmus, and anterior splenium. Global callosal measures correlated significantly with duration of illness and symptom score, and at trend level with degree of filipin staining. Measures of reflexive saccadic peak velocity and gain, and self-paced saccades, correlated strongly with total callosal area. CONCLUSIONS: Callosal structure and size reflect both state and trait markers in adult NPC, and they may be useful biomarkers to index both white and gray matter changes that reflect illness severity and progression. CrcreatineDTIdiffusion tensor imagingFEFfrontal eye fieldNPCNiemann-Pick disease type C